2016
DOI: 10.1136/oemed-2015-103507
|View full text |Cite
|
Sign up to set email alerts
|

Lifting and exertion injuries decrease after implementation of an integrated hospital-wide safe patient handling and mobilisation programme

Abstract: Objective With increasing emphasis on early and frequent mobilisation of patients in acute care, safe patient handling and mobilisation practices need to be integrated into these quality initiatives. We completed a programme evaluation of a safe patient handling and mobilisation programme within the context of a hospitalwide patient care improvement initiative that utilised a systems approach and integrated safe patient equipment and practices into patient care plans. Methods Baseline and 12-month follow-up su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 30 publications
1
30
1
Order By: Relevance
“…Musculoskeletal injury risk also showed a decreasing pattern although the finding was not significant. Many institutional‐level intervention studies have reported positive effects of SPH programs on musculoskeletal injury reduction . In our study, risk reduction was not observed for minor symptom parameters.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Musculoskeletal injury risk also showed a decreasing pattern although the finding was not significant. Many institutional‐level intervention studies have reported positive effects of SPH programs on musculoskeletal injury reduction . In our study, risk reduction was not observed for minor symptom parameters.…”
Section: Discussioncontrasting
confidence: 63%
“…Following the implementation of these standards, evaluation research is needed to assess the impact and effectiveness of the SPH law on hospital programs and practices and musculoskeletal injury prevention. While there are reports of positive outcomes of SPH programs at a single hospital or health systems level, limited data exist on the statewide impact of SPH legislation. Only Washington State evaluated the impact of SPH legislation and reported reduction of workers’ compensation claim rates from musculoskeletal disorders …”
Section: Introductionmentioning
confidence: 99%
“…The systematic search for literature resulted in 11 included studies from 12 articles published in 1999 to 2017 [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Ten of these studies were CBA studies [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 55 , 56 ] and one was an RCT [ 57 ]. Four of the studies were conducted in Canada, four in the USA, and one each in Italy, The Netherlands, and Great Britain.…”
Section: Resultsmentioning
confidence: 99%
“…Quasi-experimental studies may include evaluations of interventions initiated by employers, such as comparisons of change between intervention sites and comparison sites not randomly assigned to the intervention condition. 16 Because of the nonrandom selection, sophisticated statistical techniques like multivariate analysis, propensity score matching/weighting, coarsened exact matching, instrumental variable analysis, and other adjustment methods are used to control for confounders. 17–19 …”
Section: Discussionmentioning
confidence: 99%